The Association Between Afghan Refugees’ Food Insecurity and Socio-economic Factors in Iran: A Case Study of Khorasan Razavi Province - Khakpour, Mahasti; Khorshahi, Azar; Pakravan Charvadeh, Mohammad Reza; Omidvar, Nasrin; Engler-Stringer, Rachel; Koc, Mustafa; Garcea, Joe; White, Judy; Henry, Carol; Nematy, Mohsen; Vatanparast, Hassan (Border Crossing, 2021)
Afghan refugees are one of the most vulnerable migrant groups in terms of food insecurity status around the world. We aimed to investigate the association between Afghan protracted refugees’ food insecurity and its socio– economic determinants in Mashhad, Iran. In a cross– sectional design, information was gathered through face– to– face interviews with 299 Afghan main income earners or his/her representative in Golshar district, Mashhad, Iran. In a quantitative approach, the association of socio– economic factors with food insecurity was assessed. The results showed that less than 1% of all the households were food secure, 69.2% of those with children and 47.5% of those with no child faced severe food insecurity. Class of households’ income, residency status and personal dwelling were significantly associated with severe food insecurity of Afghan refugees. Determining effective socio– economic factors to formulate appropriate policies and practices is not only necessary but also inevitable to assure sustainable food security for refugees.